Penerapan Strategi Pembelajaran Inkuiri dalam Pembelajaran Tematik Terpadu di Kelas IV Sekolah Dasar (Studi Literatur) - Mesyta Putri Ayu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to describe the application of inquiry learning strategies in integrated thematic learning in grade IV elementary schools. This research is motivated by learning that is still teacher center, the teacher does not provide direct experience, learning seems inflexible so that students are less active in learning. Inquiry learning strategy is a learning strategy that places students as learning subjects who are given extensive opportunities to carry out activities to observe, investigate, conduct experiments by emphasizing critical and analytical thinking processes to find answers to question they ask themselves with or without the help of the teacher. This study uses the method of literature study through literature review to strengthen the analysis of various sources used. Research data collection was carried out by researchers by browsing articles contained in online journals using google scholar and documentation studies in libraries. The keywords used for journal search are inquiry learning strategies, thematic integrated. From result of the analysis of 15 articles, it shows that the application of inquiry learning strategies is effective for integrated thematic learning in primary schools.